If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m in (-oo:+oo)
3*m*(m-(7/2)) = 0
3*m*(m-7/2) = 0
( 3*m )
3*m = 0 // : 3
m = 0
( m-7/2 )
m-7/2 = 0 // + 7/2
m = 7/2
m in { 0, 7/2 }
| 6x-sqrtx=12 | | 4/5x-10=54 | | f(x)=[x-3] | | 91+19m=376 | | 15x+45x-4y= | | 34n-104=338 | | 6m+6.75=63.75 | | 5x^2-6x=4x^2+6x-13 | | 2a+2x+x=70 | | 3x-69=27 | | 4y+7z=17 | | x=385 | | 4n-7=37 | | 3n-7=17 | | 3n-7=16 | | 36z-45/9 | | -16x^2+64x-0=60 | | log(x)+log(x-5)=log(6x) | | -5.7=4.2+b | | 5x-3(6)= | | 1.3=-4.8+a | | -2x/5-4-5 | | x+8.5=10.6 | | 14y^2-12y+3= | | t-2.6=1.2 | | =4x^2+20x-11 | | x^2-4y^2-x+2y=0 | | 12+16=5x | | kx^2+kx+1=4(x^2+x) | | -13/2= | | (3y-8)(5y+2)=y | | 2u^3(5u+2)(u+3)=a |